Pengaruh Model Team Games Tournament Berbantuan Media Baamboozle Terhadap Kemampuan Berpikir Kritis Siswa SD - Fany Riyanawati; Hisny Fajrussalam; Nenden Permas Hikmatunisa (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2026)
Critical thinking skills are one of the essential competencies that elementary school students need to possess in order to meet the demands of 21st-century learning. The development of critical thinking skills is a key focus in elementary education because it contributes to improving the quality of learning and students’ readiness to tackle various complex problems. However, findings from field observations and previous research indicate the opposite—that the critical thinking skills of elementary school students have not yet developed optimally. This study aims to analyze the effect of implementing the TGT model supported by the Baamboozle media on the critical thinking skills of elementary school students and to determine the improvement in critical thinking skills among students who received instruction using the Team Games Tournament model supported by the Baamboozle media compared to students who received instruction using the Think Pair and Share model supported by the Baamboozle media. This study employed a quasi-experimental method using a non-equivalent control group design. The sample consisted of fifth-grade students at SDN Harapan Mulya I, comprising 23 students in the experimental group and 23 students in the control group. Research data were collected through critical thinking ability tests administered before and after the intervention and were subsequently analyzed using inferential statistical tests. The results show that the implementation of the TGT model supported by the Baamboozle media had a 58.5% effect on students’ critical thinking skills, and that the improvement in critical thinking skills among students who participated in learning using the TGT model supported by Baamboozle was higher than that of students who participated in learning using the TPS model supported by Baamboozle. Thus, the TGT model supported by Baamboozle media can serve as an effective alternative for IPAS instruction in supporting the development of critical thinking skills among elementary school students.